2020
DOI: 10.1021/acs.analchem.0c04055
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Gastric Cancer Circulating Tumor Cellular CLDN18.2 RNA Detection Based on a Molecular Beacon

Abstract: Gastric cancer (GC) is a major global cancer burden, and only HER2-targeted therapies have been approved in first line clinical therapy. CLDN18.2 has been regarded as a potential therapeutic target for gastrointestinal tumors, and global clinical trials have been in process. Hence, the precise, efficient, and noninvasive detection of CLDN18.2 expression is important for the effective application of this attractive target. A high similarity of protein sequence between CLDN18.1 and -18.2 made RNA become more sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…As a new approach, the CLDN18.2 molecular beacon (MB) with a stem-loop hairpin structure was reported for the detection of CLDN18.2 in blood samples. This MB rapidly recognized the RNA of CLDN18.2 [ 104 ] and was successfully applied to the circulating tumor cell (CTC) assay. This new method of detecting CLDN18.2 RNA in CTCs may be a new approach for identifying potential patients with CLDN 18.2 target drugs.…”
Section: Cldn Expression In Gcmentioning
confidence: 99%
“…As a new approach, the CLDN18.2 molecular beacon (MB) with a stem-loop hairpin structure was reported for the detection of CLDN18.2 in blood samples. This MB rapidly recognized the RNA of CLDN18.2 [ 104 ] and was successfully applied to the circulating tumor cell (CTC) assay. This new method of detecting CLDN18.2 RNA in CTCs may be a new approach for identifying potential patients with CLDN 18.2 target drugs.…”
Section: Cldn Expression In Gcmentioning
confidence: 99%
“…Targeting a single protein has limited use for the treatment of gastric cancer because of the complex pathogenesis of this disease. Indeed, although several clinical studies have explored the effects of targeted therapies alone or in combination with chemotherapies for gastric cancer, currently only ramucirumab (anti-VEGFR2) and trastuzumab (anti-ErbB2) have been approved as gastric efficient targeted drugs ( 63 ). Therefore, the combination of targeted drugs with conventional therapies might provide new opportunities for cancer treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that 92% of the protein sequence of CLDN18.1 is consistent with CLDN18.2, the search for more specific anti-CLDN18.2 antibodies remains a major challenge [ 38 ]. An alternative ultrasensitive detection method to detect circulating tumor cellular CLDN18.2 RNA based on a molecular beacon demonstrated promising potential [ 66 ]. Furthermore, studies in patients from Korea and Japan revealed that 74.4 and 87% of patients had positive expression, and in these populations, 29.4 and 40% of patients had high expression levels, respectively.…”
Section: Introductionmentioning
confidence: 99%